Imaging neuroendocrine tumours with radiolabelled somatostatin analogues and X-ray computed tomography: a comparative study. - King, C; Reznek, R; Bomanji, J; Ur, E; Britton, K; Grossman, AB; Besser, G (1993)
Various endocrine neoplasms, including a number of carcinoid and pancreatic islet cell tumours, express somatostatin receptors. These tumours may be difficult to localize using conventional techniques. Radiolabelled somatostatin analogues 123I-Tyr-3-octreotide and 111In-pentatreotide have been used for imaging these tumours. In a retrospective study of 24 patients, the sensitivities of somatostatin receptor scintigraphy and X-ray computed tomography (CT) were compared. Ten patients were scanned using 123I-Tyr-3-octreotide and 14 with 111In-pentatreotide. All patients had CT scans. Twenty patients had neuroendocrine tumours with a total of 45 lesions in the anatomical areas included on both scans. CT detected 42 while somatostatin receptor scanning detected 31 of these lesions. Three lesions were missed by CT which were detected by scintigraphy, and there were six CT false positive lesions. In a further four patients investigated for suspected neuroendocrine tumours, no lesion was shown using either modality and subsequent investigations and clinical follow-up have shown no evidence of a tumour. We conclude that while CT is more sensitive than somatostatin receptor scintigraphy, the techniques are complementary, especially in patients with disseminated pathology, equivocal lesions on CT, or a negative CT and strong clinical or biochemical evidence of a neuroendocrine tumour.